Effect of fibrous concentrate supplementation on the reproductive performance of alpacas in the Peruvian highlands - Rojas, Doris Alexandra (2021)
The aim of this study was to evaluate the effect of the supplementation of fibrous concentrate in the diet on the reproductive performance of alpacas in traditional breeding in the dry Puna of the Peruvian Andes at 4090 m of altitude to increase the fertility and birth rate, weight and body condition of the mothers, and weight at birth. In total, 60 females from first to third parity, with similar weights (37.8 ± 1.2 kg) and body condition (2.31 ± 0.42) were distributed into a supplemented group and a group without supplementation. The fibrous concentrate was prepared with ground hay (12 mmø) of oats and alfalfa, barley bran, soybean meal, vitamin and mineral mix, common salt and molasses (ME 2.48 kcal/g and CP 12%). The supply of the concentrate started 10 days before calving, at a rate of 200 g/day/animal, continuing during calving, mating, gestation, until the next calving. The mating was controlled, alternate and free. The fertility rate was determined by the sexual behavior of the females. The results indicate that the fertility rate (83.3 vs. 66.7%), birth rate (83.3 vs. 50.0%), weight at birth (5.15 vs. 3.26 kg), final weight of dams (44.6 vs. 39.2 kg) and final body condition of dams (3.97 vs. 2.77) were significantly higher with supplementation (p <0.05). It is concluded that the supplementation of fibrous concentrate prior to calving and during breeding and gestation has a positive effect on the reproductive performance of alpacas in traditional breeding.